2020
DOI: 10.17507/tpls.1009.02
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning English as a Second Language in Nigeria: Examining Evolving Approaches and Methods

Abstract: This paper examines language teaching and learning theories in a bid to consider evolving and appropriate approaches and methods for efficient teaching and learning English as a second language in Nigeria. While traditional approaches do provide a solid foundation for effective language teaching, they do not always address students' situational and current needs. Hence, the study reveals that strategies and methods are evolving especially, in this hi-tech age, to meet such additional needs. Since no one theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…As Adebileje and Akinola (2020) put it, language is an instrument of thought which binds human society together in communication and linguistic groups. Sapir (1921) defines it as a purely human and non-instinctive method of communicating ideas, emotions and desires utilizing voluntarily produced symbols.…”
Section: The Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…As Adebileje and Akinola (2020) put it, language is an instrument of thought which binds human society together in communication and linguistic groups. Sapir (1921) defines it as a purely human and non-instinctive method of communicating ideas, emotions and desires utilizing voluntarily produced symbols.…”
Section: The Backgroundmentioning
confidence: 99%
“…Aiyaubola (2012), describes language as a human vocal noise or the graphic representation of that noise used systematically and conventionally by a group of people in a community. Although several studies have been carried out on the subject of English as a second language in Nigeria, little attention has been accorded to teaching and learning processes for the English language in Nigeria (Adebileje & Akinola, 2020;Banjo, 2016;Akindele & Adegbite, 2009). On this premise, the present study attempts to examine the problems of teaching and learning English as a second language from the perspective of a theoretical framework.…”
Section: The Backgroundmentioning
confidence: 99%
“…However, it does not sound right if these two important skills are ignored. Adebileje & Akinola (2020) in their research suggested that both grammar and communication skills are equal importance in which language users -beforehand -need to be equipped with grammar rules in order to be communicative competence. This finding answers RQ1 which investigates how interaction and transaction -in the second language -are being used amongst the university students and also the consequences.…”
Section: Figure 2: Interaction and Transaction In Speakingmentioning
confidence: 99%
“…Ufomata (1996) noted that the use of English in an ESL context like Nigeria is formal with ESL speakers having different levels of proficiency and a recognisable division between mainstream educated spoken Nigerian English as in other ESL contexts. In Nigeria today, English functions as the language of education and instruction; media and politics including the judicial system hence, attention is often given to English language pedagogy (Adebileje & Akinola, 2020). For this reason, this study's concern is to propose a hybrid method of combining the brick-and-mortar classroom teaching style as well as digital technology to improve English pronunciation among Nigerian learners of English as a second language.…”
Section: Introductionmentioning
confidence: 99%